Changes in Physical Activity and Sedentary Behaviors During COVID-19: Associations with Psychological Distress Among Mothers - de Brito JN; Friedman JK; Emery RL; Neumark-Sztainer D; Berge JM; Mason SM (Dove Medical Press, 2021)
Junia N de Brito,1 Jessica K Friedman,1 Rebecca L Emery,2 Dianne Neumark-Sztainer,1 Jerica M Berge,3 Susan M Mason1 1Division of Epidemiology and Community Health, University of Minnesota, Minneapolis, MN, USA; 2Department of Family Medicine and Biobehavioral Health, University of Minnesota, Duluth, MN, USA; 3Department of Family Medicine and Community Health, University of Minnesota, Minneapolis, MN, USACorrespondence: Junia N de BritoDivision of Epidemiology and Community Health, University of Minnesota, 1300 S 2nd St, Suite 300, Minneapolis, MN, 55455, USATel +1 612-624-1818Email nogue013@umn.eduBackground: The coronavirus disease 2019 (COVID-19) pandemic increased mothers' caregiving demands, potentially placing them at increased risk for reduced engagement in healthful behaviors and high psychological distress.Purpose: The purpose of this study was to describe perceived changes in moderate-vigorous physical activity (MVPA) and sedentary behaviors and the prevalence of different measures of psychological distress (depressive and anxiety symptoms, perceived stress, and positive and negative affect) among mothers. We also evaluated the associations of perceived change in MVPA and sedentary behaviors with measures of psychological distress.Methods: We conducted a cross-sectional survey with 317 mothers living with children (0- 20 years old) at home. Mothers self-reported perceived changes in MVPA and sedentary behaviors from before the pandemic to during COVID-19 stay-at-home orders and early reopening, and levels of depression and anxiety symptomatology, perceived stress, and positive and negative affect during the pandemic.Results: Compared to pre-pandemic levels, 39% of mothers reported engaging less in MVPA, and 63% reported engaging in more sedentary activities. One-quarter and 31% of mothers reported moderate/severe depressive and anxiety symptoms, respectively, and 78% medium/high levels of perceived stress. Adjusted linear regression analyses revealed that reduced MVPA and increased sedentary behaviors were associated with high average scores of depressive and anxiety symptoms, perceived stress, negative affect, and low scores of positive affect.Conclusion: A large proportion of mothers reported being less physically active and more engaged in sedentary behaviors, which were associated with increases in psychological distress. Clinical and public health intervention efforts should consider how to improve mothers' physical and mental health as the country emerges from this crisis.Keywords: COVID-19, mothers, physical activity, stress, depression, anxiety